PSIDIUM JUICE GUAJAVA LINIMENT AGAINST INCREASED HEMOGLOBIN IN PREGNANT WOMEN (Proceedings OPTIMAL, 2026)
Pregnancy experiences both physiological and psychological changes, such as an increase in blood volume and an imbalance in the number of red blood cells due to a much greater increase in plasma volume, causing a decrease in hemoglobin levels. Anemia in pregnant women has negative impacts on the health of the mother and fetus, such as the risk of postpartum hemorrhage, the risk of premature labor, low birth weight, and impaired fetal growth and development, and can even cause maternal and fetal death. Consuming foods or drinks rich in iron and vitamin C, which can help increase hemoglobin levels in the blood. Red guava juice is contains 1.10 mg of iron and 87 mg of vitamin C per 100 grams. This research determine the effect of red guava juice on increasing hemoglobin levels in pregnant women. This used a quasi-experimental design with a pretest-posttest approach without a control group. The respondents was 33 pregnant women, consisting of 13 primiparous and 20 multiparous. Respondents were given an red guava juice, consisting of 100 grams of fresh red guava in 150 ml of juice, daily for 7 days. Results that the average hemoglobin level before the intervention was 12.6 g/dL, while after the intervention it increased to 13.4 g/dL. This increase indicates a positive effect of red guava juice consumption on hemoglobin levels in pregnant women. The conclusion is that red guava juice has the potential to be a natural alternative to increase hemoglobin levels in pregnant women, both primiparous and multiparous.